2016
DOI: 10.2500/ar.2016.7.0149
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 and Anti-heat Shock Protein 70 Antibodies in Nasal Secretions of Patients with Chronic Rhinosinusitis

Abstract: Background:The issue of heat shock protein (HSP) 70 and anti-HSP70 antibodies in chronic rhinosinusitis (CRS) has never been explored.Objective:To determine the nasal secretion (NS) levels of HSP70 and anti-HSP70 antibodies in patients with CRS with nasal polyps (CRSwNP) and patients with CRS without nasal polyps (CRSsNP), and to evaluate their associations with CRS clinical severity and correlation with NS interleukin (IL), IL-5 and interferon λ.Methods:CRS severity was determined by Lund-Mackay scores. Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 38 publications
(40 reference statements)
0
18
0
1
Order By: Relevance
“…[3][4][5] Recent studies demonstrated that apoptotic and necrotic cells release damage-associated molecules, such as heat shock proteins (HSPs), that promote early innate and adaptive immune responses. 6,7 HSP70 is the best-studied damage-associated molecule. It stimulates the maturation of dendritic antigen-presenting cells and activates the nuclear factor kappa B (NF-κB) pathway, which modulates production of several cytokines.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5] Recent studies demonstrated that apoptotic and necrotic cells release damage-associated molecules, such as heat shock proteins (HSPs), that promote early innate and adaptive immune responses. 6,7 HSP70 is the best-studied damage-associated molecule. It stimulates the maturation of dendritic antigen-presenting cells and activates the nuclear factor kappa B (NF-κB) pathway, which modulates production of several cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…9 The concentrations of HSP70 in nasal secretions are increased in patients with NP and correlate positively with the severity of sinus disease and the levels of IL-4 and IL-5 in nasal fluid. 6,7 Many biomarkers of inflammation can be detected in nasal secretion samples and they can reflect the inflammatory status of the nasal mucosa and progression of mucosal disease. In the present study, we compared the levels of HSP70, eosinophil cationic protein (ECP), tryptase, substance P, and Clara cell protein…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…В последние годы отмечен значитель ный рост распространенности заболевания слизистой оболочки носа (риниты) и око лоносовых пазух (риносинуситы) [9]. Дан ные патологии чаще всего характеризуются синдромом, который включает заложен ность носа, ринорею, приступы чихания, головную боль и другие, что отрицательно сказывается на социальных, физических и психических аспектах жизни человека [1].…”
Section: Introductionunclassified